PEMAKNAAN DIRI KLIEN LAKI-LAKI PASCA KONSELING LAKI- LAKI DALAM KASUS TINDAK KEKERASAN DALAM RUMAH TANGGA DI RIFKA ANNISA - SUNDARI, ANY; PARTINI, PARTINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
For nearly 20 years working on issues of violence against women, Rifka Annisa as psychosocial services agency that helps abused women find the handling of the data that surprising. More than 90% of women victims of violence who come to ask for help Rifka Annisa decided to return to the couple (the husband) and did not take the path of divorce or criminal cases of violence reported that they experienced .. This fact encourages Rifka Annisa to provide counseling services for men male (spouse), because women back on couples naturally prone to remain in the cycle of violence if they do not intervene. The purpose of this study is to look at the meaning of the man himself after the domestic violence counseling men in Rifka Annisa. The formulation of the problem is how the meanings themselves men of domestic violence counseling after they did Rifka Annisa on. The subjects of this study were three men who conduct counseling behavior change, where one informant conduct mandatory counseling and two informants based on the request of his wife. The method used is a qualitative method with a phenomenological approach. The results showed violence perpetrated by men formed due to the form of knowledge that is inherent in them as a way of life that is set up in everyday life as objectification . Violence is reasonable because since childhood men live in the cycle of violence ( JS & AF ) in the family They experience conflict within themselves when not managed to achieve the cultural construction of society how to be the ideal man . In all three cases is the inability to meet economic needs ( JS & CH ) , can not control the ex- wife who eventually separated from the client ( CH ) . The condition is then pushed men experiencing crises themselves and vent to her partner . Form of externalization or adjustment to change the violence carried out by his third wife after they reported that they had experienced domestic violence in the Rifka Annisa . They are encouraged to make adjustments and negotiations on the conditions of this conflict for reasons they do not want to be apart of couples split up because if they fail to control it means the wife , they are afraid to away from the kids and the pressure through mandatory counseling law into consideration the underlying terms of the male to adjust to the couple . After the counseling they reflect the concept of themselves as men who are influenced by cultural construction , which gives them the legitimacy to do violance . They compared the positive effects when they do not live in a cycle of violence , to convince themselves that they actually do not like it and could change . Internalize the concept of self to give up violence driven by the motivation of the family ( wife and children ) that he can change and it is very significant for men . This impulse is reflected in the attitudes and behaviors of men who could manage emotions , sharing roles and provide space for women to thrive. In the internalization stage of post-counseling, it can be seen that the male has space for deconstructing the meaning of themselves as men in order to form the male construction more broadly to not commit violence against the couple.